Keefektivan metode simulasi dan metode brainstorming untuk meningkatkan pengetahuan kesehatan reproduksi remaja - Wiwik NorMa , Ova Emllla, Siswanto Agus Wilopo (Berita Kedokteran Masyarakat (BKM), 2005)
Background: Early education on reproductive health helps teenagers to have responsible attitude and behavior. Integrating reproductive health education in the school curricula is a very important strategy. Methods of education which can improve effectiveness of knowledge dissemination on reproductive health needs to be identified, Objective: To understand the effectiveness of simulation and brainstorming methods to Increase teenagers knowledge on reproductive health. Method: This was a quasi experimental study which used pre test-post test control group design. Samples were divided into two groups simulation and brainstorming. There were 160 respondents age 10-12 years old. Samples were purposively selected considering their basic characteristics. Data analysis used paired t-test, independent Hest and double linear regression analysis with significance 95%